Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1038/s41598-021-00716-6
|View full text |Cite
|
Sign up to set email alerts
|

Flexible emotion regulatory selection when coping with COVID-19-related threats during quarantine

Abstract: The COVID-19 pandemic poses significant emotional challenges that individuals need to select how to regulate. The present study directly examined how during the pandemic, healthy individuals select between regulatory strategies to cope with varying COVID-19-related threats, and whether an adaptive flexible regulatory selection pattern will emerge in this unique threatening global context. Accordingly, this two-study investigation tested how healthy individuals during a strict state issued quarantine, behaviora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 51 publications
1
6
0
Order By: Relevance
“…Our results indicated that if without adaptive behaviors, the total infection in these countries could be 3.68, 26.16, 15.23, 4.23, 7.26, 1.65, 5.51 and 7.07 times as large as reported. Our estimation of NPI outcome is consistent with existing research ( Teslya et al, 2020 , Anon, 2021 , Shabat et al, 2021 ). Hence it is very necessary to maintain media publicity and government guidance during epidemic transmission.…”
Section: Discussionsupporting
confidence: 90%
“…Our results indicated that if without adaptive behaviors, the total infection in these countries could be 3.68, 26.16, 15.23, 4.23, 7.26, 1.65, 5.51 and 7.07 times as large as reported. Our estimation of NPI outcome is consistent with existing research ( Teslya et al, 2020 , Anon, 2021 , Shabat et al, 2021 ). Hence it is very necessary to maintain media publicity and government guidance during epidemic transmission.…”
Section: Discussionsupporting
confidence: 90%
“…Prior research has demonstrated that selecting reappraisal (instead of distraction) for low-intensity emotional stimuli and selecting distraction (instead of reappraisal) for highintensity emotional stimuli confers a neuro-affective benefit, of larger Latent Positive Potential modulation, and (in instances where reappraisal is chosen instead of distraction for low-intensity stimuli) better memory of the emotional information (Ilan et al, 2020;Shafir et al, 2016;Sheppes, 2020). Furthermore, previous studies have found that participants who adopt this pattern of regulatory selections also exhibit better psychological functioning (Fine et al, 2021;Shabat et al, 2021). It is, thus, unexpected that in our trial-level analysis we did not find reappraisal choices to result in lower negative affect than distraction choices for lowintensity images, or distraction choices to result in lower negative affect than reappraisal choices for high-intensity images.…”
Section: Discussionmentioning
confidence: 98%
“…Consequently, the regulatory selection paradigm operationalizes regulatory selection flexibility as a greater tendency to select distraction in response to high-intensity emotional stimuli, and reappraisal in response to low-intensity emotional stimuli (Fine et al, 2021; Levy-Gigi et al, 2016; Shabat et al, 2021). In the regulatory selection paradigm (Sheppes et al, 2011), participants view a series of negative images and, for each image, are prompted to choose either reappraisal or distraction to help reduce their negative emotion while viewing that image.…”
mentioning
confidence: 99%
“…Within the context of the current COVID-19 pandemic, many studies have examined the use of coping strategies to counteract stressful situations (Bendau et al, 2021 ; Panayiotou et al, 2021 ; Prati, 2021 ), but only a minute number have looked at flexible use of coping and regulation strategies (Shabat et al, 2021 ) finding differential use of strategies depending upon the individual and their context. Although the flexible application of our proposed processing mechanisms, including coping and regulation strategies along with the biological and neural mechanisms, within the pandemic context needs further investigation, it becomes evident that these processing mechanisms modulate the influence of the various predictor factors to lead to resultant resilient or vulnerable functioning.…”
Section: Processing Mechanismsmentioning
confidence: 99%